Pembentukan Sikap Keberagamaan Peserta Didik Melalui Kegiatan Pesantren Sabtu Ahad (PETUAH) - Abdurahman, Ade Mohamad; Suhartini, Andewi (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2023)
This paper is motivated by the moral decline of high school students which is a reflection of their religious attitude, which has an impact on poor relations with educators, lack of enthusiasm in learning and not yet visible self-awareness in carrying out daily worship. This happens because of the weak diversity of students. Therefore, this paper will describe how educators can shape students' religious attitudes through religious extracurricular activities. The stages of forming a religious attitude are implemented in an activity at the Saturday Sunday Islamic boarding school (PETUAH). The results of the study found that to form religious attitudes, students are not only equipped with cognitive knowledge about how they worship vertically and get along with fellow humans in horizontal relationships, but also must arrive at the affective realm and be implemented in real behavior.